Peran Gaya Kepemimpinan Dalam Meningkatkan Mutu Pendidikan Madrasah Di Provinsi Banten - R. Asep Hidayat Sugiri; Encep Syarifudin; Anis Fauzi (Tadbir: Jurnal Manajemen Pendidikan Islam, 2022)
Understanding the role of leadership style in the form of transactional leadership style, transformative leadership style and visionary leadership style in improving the quality of madrasa education in Banten Province, including exposing the supporting and inhibiting factors. This research uses literature study method. The author examines the existing problems by examining several books and related journal articles to compare and draw conclusions. The results of this study show the following: First, the leadership style of Madrasah directors in Banten Province is very different, especially at the research site, namely some have developed a transactional leadership style (the academic community of MAN 1 Serang City), some have developed a transformative leadership style (the MAN 2 Kota Serang academic community). Attack), and some of them develop visionary leadership styles (the academic community of MAN 1 Serang Regency). Second, the different leadership styles of madrasah directors practiced in different locations with different leadership styles play a significant role in efforts to improve the quality of madrasah education in Banten Province.